Female infanticide in India and its relevance to Nepal - Vickery, Michelle; Teijlingen, Edwin van (Journal of Manmohan Memorial Institute of Health Sciences, 2018)
This paper offers a sociological analysis of female infanticide in India with the aim of provoking readers to consider similar issues in Nepal. India and Nepal have a close relationship; their citizens are able to travel freely between the two countries and they share many similarities in their cultural, religious and social traditions. This has meant that people and ideas are easily exchanged between the two, making it necessary to consider the Indian phenomenon of female infanticide in Nepalese context. Journal of Manmohan Memorial Institute of Health Sciences Vol. 3, No. 1, 2017, page: 79-85